2015
DOI: 10.3389/fimmu.2015.00586
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocyte Migration: An Action Movie Starring the Actin and Associated Actors

Abstract: The actin cytoskeleton is composed of a dynamic filament meshwork that builds the architecture of the cell to sustain its fundamental properties. This physical structure is characterized by a continuous remodeling, which allows cells to accomplish complex motility steps such as directed migration, crossing of biological barriers, and interaction with other cells. T lymphocytes excel in these motility steps to ensure their immune surveillance duties. In particular, actin cytoskeleton remodeling is a key to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 176 publications
(204 reference statements)
3
95
1
Order By: Relevance
“…From this disease, it has shown that the lack of CD18 causes adhesion and mobility deficiencies that result in multiple skin infections and slow wound healing(36). Consistent with established data, we have shown that CD18 is ubiquitously expressed on all lymphocytes in the peripheral blood(15, 25). The levels of lymphocyte CD18 expression were unchanged by the clinical circumstances with all groups displaying approximately 100% expression.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…From this disease, it has shown that the lack of CD18 causes adhesion and mobility deficiencies that result in multiple skin infections and slow wound healing(36). Consistent with established data, we have shown that CD18 is ubiquitously expressed on all lymphocytes in the peripheral blood(15, 25). The levels of lymphocyte CD18 expression were unchanged by the clinical circumstances with all groups displaying approximately 100% expression.…”
Section: Discussionsupporting
confidence: 91%
“…T-lymphocytes use integrins to migrate in and out of lymph nodes and, following infection, to migrate into other tissues(14, 17, 18, 25). Integrins are key to the immunological cross-talk between T cells and antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these data obtained with the amoeboid migration of lymphocytes model confirm the intense relation of clathrin and clathrin‐related proteins with the molecular machinery controlling actin rearrangements. Actin plays a major role in lymphocyte migration (and polarization) by controlling the dynamics of the cell shape during migration . Here, we show a model that integrate the motility signals triggered by the chemokines into coordinated actin rearrangements, being clathrin a key protein in this process that recruits the molecular machinery able to promote actin polymerization, similarly to what was observed in other biological processes .…”
Section: Discussionmentioning
confidence: 69%
“…The migration of T cells is regulated by spatial and temporal cytoskeletal remodeling . Actin filaments are distributed radially in resting T lymphocyte, and polymerize into branches upon chemokine receptor or LFA‐1 engagement .…”
Section: Introductionmentioning
confidence: 99%